Comparison between Erlang B and Erlang C for typical mobile radio traffic / Marahakim Manap - Manap, Marahakim (2001)
The aim of this project is to present the comparison between Erlang B (loss call) and Erlang C (queue call) traffic for mobile radio environment. The data on traffic performance on mobile radio in Klang Valley area are collected and analyzed using a computer package called MATLAB